Fine Motor Stimulation of Children Through Coloring Activities in Early Childhood - Besse Marhaeni; Idha Septriana; Sovia Wahyuning Suci (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2022)
This study examines the stimulation of children's fine motor skills through image coloring activities in group B of Dharma Wanita Majauleng Kindergarten, Wajo Regency. This research uses a quantitative approach with the type of research, the one-group pretest-posttest design. The sample in this study was 11 children. The data collection technique uses Pretest–Posttest Design, and the results are analyzed using descriptive quantitative. The results of the image coloring activity on the improvement of children's delicate motor stimulation showed that the measurement data from the pretest, the fine motor ability of students in the learning completion value of the low category. The results of post-test scores show that the average value of students' fine motor skills is very high, with classical learning completion scores achieved by all children. This study shows that the activity of coloring children's drawings can train children's strength in holding writing stationery so that students are trained to develop their fine motor skills.